If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -6) = 22 Reorder the terms: 4(-6 + x) = 22 (-6 * 4 + x * 4) = 22 (-24 + 4x) = 22 Solving -24 + 4x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 4x = 22 + 24 Combine like terms: -24 + 24 = 0 0 + 4x = 22 + 24 4x = 22 + 24 Combine like terms: 22 + 24 = 46 4x = 46 Divide each side by '4'. x = 11.5 Simplifying x = 11.5
| 12-2x-10=20 | | 4(4x+6)=3(2x+12) | | t+2c= | | (2x^2)+7x-5=0 | | x+3x+1.5x=180 | | 7y=3x-23 | | (4-2x)=24 | | 5p^2-34+24= | | 8/9+i=0 | | g(x)=8 | | g(6)=8 | | 6y-12=5y-10 | | -3-(8x-4)=3(x+2)+7 | | -14x+7=21 | | -x-2(x+1)=1-7x | | 3(2x+8)=2(2x+40) | | 10x-7y=44 | | 5+2(x+3)=-x-6 | | 0=t^2+t-6 | | a+5=-16 | | -3(5+7p)=33-5p | | -2(x+7)=4x-7 | | -4=13.7 | | 15-3x=12-5x | | 4w(w-6)-2w^2=2w^2+8w-4 | | 2+3n=0.8n+18 | | 14-x=3x-2 | | x^3+5x^2+16x+80=0 | | 4/28=x/147 | | -7(x-6)-8=-5x+40 | | 5W+W=36 | | h=9(8m-9r) |